Correlation of Curricular Transition Quality with the Religiosity and Morality Index of University Students - Ace Somantri; Muhammad Hisyam Syafii; Amirudin Amirudin; Rudyn Alaldaya; Husain Azhari (IJECA (International Journal of Education and Curriculum Application), 2026)
This study aims to examine the relationship between curricular transition quality and the religiosity–morality index of university students within the context of higher education reform. Contemporary curriculum changes increasingly emphasize holistic student development, including ethical and spiritual dimensions; however, empirical evidence on their impact remains limited. A quantitative correlational design was employed involving 285 undergraduate students who experienced both previous and newly implemented curricula at Universitas Muhmmadiyah Bandung. Data were collected using the Curricular Transition Quality Questionnaire (32 items) and the Religiosity–Morality Index Scale (28 items). Both instruments demonstrated strong psychometric properties, with factor loadings ranging from 0.724–0.892, Average Variance Extracted (AVE) above 0.50, Composite Reliability exceeding 0.90, and Cronbach’s alpha values above 0.89, indicating adequate validity and reliability. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal a significant positive relationship between curricular transition quality and the religiosity–morality index (β = 0.584, p < 0.001), with moderate explanatory power. Among the dimensions, implementation fidelity and faculty competence emerged as the strongest predictors. In conclusion, the quality of curriculum transition plays a substantial role in fostering students’ moral and religious development, although it is not the sole determinant. These findings highlight the importance of systematic, well-supported curriculum implementation as a strategic approach to promoting holistic student development in higher education.